Takayasu's arteritis with myocarditis in infancy - A rare occurrence - Sandip Gupta; H S Guruprasad; Shivakumar Shamarao; Ashwath Ram Rao (Wolters Kluwer Medknow Publications, 2019)
Background: Takayasu's arteritis (TA) is a rarity in young children, with only less than 10 cases reported in infants worldwide, to date. Case characteristics: We report our experience with a 4-month-old girl who was diagnosed with Takayasu arteritis, presenting with myocarditis and heart failure. She had high inflammatory markers and coronary dilatation on echocardiography. She was initially treated with IVIG (intravenous immunoglobulin) and Aspirin. The persistence of high acute phase indices prompted further investigation, revealing narrowing of the major segments of the aorta, on CT angiography. Based on these angiographic findings diagnosis of TA was made. Outcome: She responded to immunosuppressive therapy. Conclusion : TA though rare, in infancy can present with unexplained myocarditis especially with elevated inflammatory markers and heart failure.